Assessing the impact of collapse of microfinance institutions on its customers in Ghana (A Case Study of The Kumasi Metropolis) - BAKU, DANIEL (2016)
A thesis submitted to the Department of Accounting and Finance Kwame Nkrumah University of Science and Technology School of Business in partial fulfillment of the requirements for the degree of Master of Business Administration (Finance Option),